Evaluation of the Relationship Between Clinical Frailty Scale (CFS) and Mortality in Geriatric Patients with Pneumonia Diagnosed in Intensive Care - Guler Eraslan Doganay; Melek Doganci; Mustafa Ozgur Cirik; Tarkan Ozdemir; Murat Yıldız; Mehtap Tunc; Maside Arı; Fatma Ozturk Yalcin; Derya Hosgun; Banu Çakıroglu; Oral Mentes; Azra Ozabarci (Medicina)
Background and Objectives: Frailty can represent the transitional stage between successful aging and old age in need of care; it is a guide for setting goals for regaining robust old age in the individual at risk. Frailty is associated with longer intensive care unit duration, hospital stay, and higher mortality. The aim of this study was to evaluate the relationship between mortality and frailty in geriatric patients (65 years and older) admitted to the intensive care unit with a diagnosis of pneumonia. Materials and Methods: In total, 478 patients were included in the study. The demographic data, such as age, gender, body mass index (BMI), Charlson comorbidity index (CCI), Clinical Frailty Scale (CFS), acute physiology and chronic health evaluation (APACHE II) scores, sequential organ failure assessment score (SOFA), invasive/noninvasive mechanical ventilator days, length of stay in the hospital and intensive care unit, inotropic requirement, and 28-day mortality, were retrospectively scanned and recorded. Results: Advanced age, lower BMI, higher Charlson Comorbidity index (CCI), SOFA score, and CFS increased 28-day mortality. CFS was found to be associated with 28-day mortality similar to the use of inotropic agents, prolonged MV duration, and ICU length of stay (LOS). Conclusions: CFS is effective in predicting 28-day mortality in geriatric patients diagnosed with pneumonia in intensive care. It also provides insights into morbidity parameters such as requirement for inotropic agents, duration of mechanical ventilation (MV), and LOS ICU.